1999
DOI: 10.1021/ma991049w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Crystalline Phase Transitions in Fluorniated vs Nonfluorinated Parylene Thin Films

Abstract: Thermally induced morphological changes in thin (1−5 μm) films of poly(α,α,α‘,α‘-tetrafluoro-p-xylylene, (C6H4CF2) n ) (Parylene-F or PPX-F) are characterized using differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD), and thermal stress measurements. A reversible crystalline phase transition is observed between 360 and 400 °C, which to our knowledge has not been reported previously. The transition is accompanied by an increase of the in-plane tensile stress of the film, which is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…As reported in the literature for PA-N, recrystallization could be accompanied by a possible change in the PA-F polymorphism, even if this has not been demonstrated to date. 19 The small peak at an angle near 2h = 16.4°that appears after annealing is due to diffraction of K b radiation from the same hightemperature crystalline plane that gives rise to the main K a peak. The length of the repeat units (d-spacing) for both as-deposited and annealed films was calculated using the Bragg equation:…”
Section: Correlation Between Conductivity and Crystallizationmentioning
confidence: 96%
See 3 more Smart Citations
“…As reported in the literature for PA-N, recrystallization could be accompanied by a possible change in the PA-F polymorphism, even if this has not been demonstrated to date. 19 The small peak at an angle near 2h = 16.4°that appears after annealing is due to diffraction of K b radiation from the same hightemperature crystalline plane that gives rise to the main K a peak. The length of the repeat units (d-spacing) for both as-deposited and annealed films was calculated using the Bragg equation:…”
Section: Correlation Between Conductivity and Crystallizationmentioning
confidence: 96%
“…These results are consistent with the works of Morgen et al, where T c was found in the range from 395°C to 403°C. 19 Figure 7 shows XRD measurements of PA-F films before and after annealing at 400°C for 1 h in N 2 . The as-deposited film presents a wide, low-magnitude diffraction peak (centered at 2h = 19.14°) characteristic of a poorly crystallized structure.…”
Section: Correlation Between Conductivity and Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[36,38] that reversible behavior can also be observed under certain circumstances. More specifically, it was suggested that, the a to b 1 phase transition in PPX is kinetically slow and can occur in the temperature range between þ200 and þ250 C, with its reversibility being dependent on the annealing conditions [38]. Perhaps, the low temperature of the a to b 1 transition observed in our study can be accounted for by the film thickness.…”
Section: Resultsmentioning
confidence: 98%